Campus sustainability in Chinese higher education institutions. Issue 1 (5th January 2015) - Lo, Kevin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the focuses, motivations and challenges of achieving campus sustainability in Chinese higher education institutions (HEIs). Design/methodology/approach – A multisite case study was conducted in Changchun City, Jilin, where eight HEIs of various types were examined. Structured interviews with school managers, students and government officials were accompanied with analysis of relevant documents. Findings – The focuses of sustainability among the studied HEIs were on water and energy conservation and on non-technical initiatives. The focuses can be explained by motivations and challenges. The HEIs are motivated by government and financial pressures and face challenges in limited accessibility to funding. The reliance of non-technical initiatives has negatively impacted student welfare and has become unpopular among students. Practical implications – The government is advised to increase funding to HEIs in relation to sustainability and to make the funding more equitable. The HEIs are advised to modify sustainability practices that severely affect the daily lives of students, to share the benefits of water and energy conservation with their students and to involve students in sustainability governance. Originality/value – This paper adds to the existing literature in two ways. First, it expands the geographical reach of the literature to developing countries, in general, and to China, in particular. Second, it adopts the multisite case study research approach to study the whole spectrum of Chinese HEIs and highlights the differences among these HEIs when it comes to sustainability.